Epidemiology of cardiovascular disease in Europe. - Townsend, Nick; Kazakiewicz, Denis; Lucy Wright, F.; Timmis, Adam; Huculeci, Radu; Torbica, Aleksandra; Gale, Chris P.; Achenbach, Stephan; Weidinger, Franz; Vardas, Panos (Nature Reviews Cardiology, 2022)
This Review presents data describing the health burden of cardiovascular disease (CVD) within and across the WHO European Region. CVD remains the most common cause of death in the region. Deaths from CVD in those aged <70 years, commonly referred to as premature, are a particular concern, with >60 million potential years of life lost to CVD in Europe annually. Although more women than men die from CVD, age-standardized rates of both morbidity and death are higher in men, and these differences in rates are greatest in individuals aged <70 years. Large inequalities in all measures of morbidity, treatment and mortality can be found between countries across the continent and must be a focus for improving health. Large differences also exist in the data available between countries. The development and implementation of evidence-based preventive and treatment approaches must be supported in all countries by consistent surveillance and monitoring, such that we can quantify the health burden of CVD as well as target interventions and provide impetus for action across Europe.
EVALuna2:482703